2011
DOI: 10.1128/iai.05209-11
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and Sufficient Role for T Helper Cells To Prevent Fungal Dissemination in Allergic Lung Disease

Abstract: Mucosal immune responses to fungal infection range from T helper type 2 (Th2) cell-directed allergic inflammation to Th1-predominant neutrophilic inflammation, but the mechanisms directing these divergent mucosal immune outcomes and the role of T cells in host defense against mucosal fungal infections are not known. Here we examined the mouse mucosal immune responses to 12 filamentous environmental fungal species over a broad range of exposure doses and determined the requirement of T cells for host defense. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 57 publications
5
49
0
1
Order By: Relevance
“…Airway Hyper-responsiveness Measurement-Measurements of airway hyper-responsiveness were conducted 24 h after the last intra-tracheal challenge with ovalbumin as previously described, with some modifications (28,29). Briefly, rats were anesthetized with etomidate and intubated for continuous ventilation inside a whole body plethysmograph using 100% oxygen to maintain physiologic pH and arterial PCO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Airway Hyper-responsiveness Measurement-Measurements of airway hyper-responsiveness were conducted 24 h after the last intra-tracheal challenge with ovalbumin as previously described, with some modifications (28,29). Briefly, rats were anesthetized with etomidate and intubated for continuous ventilation inside a whole body plethysmograph using 100% oxygen to maintain physiologic pH and arterial PCO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies from our laboratories have established that fungal sensitization in CRS is very common and that fungal growth within the airways is essential to the pathophysiology of experimental fungal allergic airway disease in mice 13-15 . We have further shown that fungal proteinases are intimately linked to both anti-fungal immunity and the expression of experimental asthma through the activation of fibrinogen and TLR4 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, PU.1, a transcriptional regulator of alternative polarization of macrophages, has been implicated in the pathological outcome of Aspergillus -induced asthmatic airway inflammation [38, 39]. Moreover, classical macrophages are a potent source of reactive oxygen species and can promote Th1 response [40, 41], both of which have been shown by our studies and others to be helpful in the control of Aspergillus infection [4248]. However, as it is becoming more apparent that the distinctions between “classical” and “alternative” are fluid characterizations, it is likely that both macrophage activation states are functionally required for mounting a robust defense against Aspergillus .…”
Section: Myeloid Responsesmentioning
confidence: 86%